Determinants of Teacher Competence in Islamic Education: Bibliometric Analysis and Approach - Fadli Agus Triansyah; Yusupov Komaliddin Bakhtiyor Ugli; Ilham Muhammad; Nurhoiriyah Nurhoiriyah (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to identify publications on teacher competence in madrasah education and describe this research's characteristics. The bibliometric analysis method was used in this study. The results showed that publications on teacher competency in madrasahs/schools increased yearly from 2017 to 2020. The highest number of documents was at the institution or university